ANALISIS PERTANIAN STROBERI DI KECAMATAN RANCABALI KABUPATEN BANDUNG - Muhammad Imam Ma'ruf; Ken Suratiyah (Agro Ekonomi, 2010)
The obectives of this research were: (1) to analyse the business feasibility of strawberry farming and (2) to determine the contribution of strawberry farming to the farmer household income. This research used description basic method. Purposive sampling was use to determine the location (the village) and simple random sampling was use to choose the respondents. The primary data were collected from 30 farmer households. The location of this research was in Alamendah village, Rancabali subdistrict, Bandung district. The result of analysis show that strawberry farming feasible to be expanded. Business feasibility were figure by average revenue cost ratio was 2,25; average income was Rp 68.731.640,88; average capital productivity was 1,25; average labour productivity was Rp 77.548,00Iman days; average BEP based on yield was 718,94 kg; average BEP based on sales was Rp 9.928.947,69; and average BEP based on output price was 6. 132, 48/kg. Average income contribution of strawberry farm to household income was 66,24 %.